HUBUNGAN PENGETAHUAN DAN SIKAP PASIEN DIABETES MELITUS DENGAN UPAYA PENCEGAHAN ULKUS DIABETIKUM DI POLI PENYAKIT DALAM RUMAH SAKIT UMUM DAERAH RADEN MATTAHER PROVINSI JAMBI - Susnia Ramayani; Shalahudden Syah (Jurnal Akademika Baiturrahim Jambi, 2016)
Background: The incidence and complications of DM are quite high evenly throughout Indonesia so it can be regarded as one of the national problems that should be paid attention. One of the most common complications of diabetes mellitus is diabetic ulcers, which can manifest as ulcers, infections and gangrene.Method: This research is a quantitative research cross sectional design is aimed to know the knowledge and attitude of diabetes mellitus patients with prevention efforts diabetic ulcers in Poly Diseases in General Hospital Regional Raden Mattaher Jambi. The study was conducted in March 2016 with a sample size of 57 respondents. Data were obtained using questioner, analyzed by univariate and bivariate, looking for correlation using chi-square test. Result: The result of research analysis is known from 57 respondents, 63,2% prevention effort not good and 36,8% good prevention effort, 66,7% have low knowledge and 33,3% have high knowledge, 54,4% have less attitude Good and 45,6% have good attitude. The result of statistical test shows that there is a significant correlation between knowledge (p-0,009) and attitude of patient (p-0,001) with prevention effort of diabetic ulcer in diabetes mellitus patient at RSUD Radi Mattaher Jambi Hospital in 2016. Suggestion: It is expected that nurses in the Poly Diseases can provide counseling about the dangers of diabetes mellitus and prevention efforts diabetic ulcers.